Expression of glnA in Escherichia coli is regulated at tandem promoters. - Reitzer, L J (1985)
We have determined that the glnA gene of the complex glnALG operon of Escherichia coli is transcribed from tandem promoters. Expression from the upstream promoter, glnAp1, requires the catabolite activating protein, is repressed by nitrogen regulator I (NRI), the product of glnG, and produces a transcript with an untranslated leader of 187 nucleotides. Expression from the downstream promoter, glnAp2, requires NRI as well as the glnF product; full expression also requires growth in a nitrogen-limited environment. The downstream transcript has an untranslated leader of 73 nucleotides. We also provide evidence that the function of the glnL product is to mediate the interconversion of NRI between a form capable of activating glnAp2 and an inactive form in response to changes in the intracellular concentration of ammonia. The function of the two minor promoters of the glnALG operon, glnAp1 and glnLp, is to maintain the products of glnA, glutamine synthetase, an essential enzyme, and of glnG, NRI, an activator of nitrogen-controlled genes, during carbon-limited growth.